The Political Economy of Rare Earth Elements - Kiggins, Ryan David. author. aut Link
XIV, 228 p.
Keywords: The contributors argue that rare earths are essential to the information technology revolution on which humans have come to depend for communication, commerce, and, increasingly, engage in conflict. They demonstrate that rare earths are a strategic commodity over which political actors will and do struggle for control.